Pengaruh Kualitas Pelayanan dan Nilai Pelanggan Terhadap Kepuasan Pelanggan PT. Anugerah Bintang Sejahtera Abadi Banyuwangi - Retno Daniati; Kadek Rai Suwena (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This research aims to examine the variables of service quality and customer value partially and simultaneously whether there is an influence on customer satisfaction at PT. Banyuwangi Eternal Prosperous Star Award. This type of research is causal quantitative and the data collection method is a questionnaire, but previously tested for validity and reliability first. A sample of 155 respondents. The sample technique uses purposive sampling and the sample conditions are according to the selected qualifications, namely users of delivery services at PT. Banyuwangi Eternal Prosperous Star Award. Data analysis methods in this research are multiple linear regression, classic assumption test, t test and f test. The results of this research show: (1) there is a partial positive and significant effect of service quality and customer value on PT. Anugerah Bintang Sejahtera Abadi Banyuwangi is proven by the t-count value of the X1 variable 4.892 > t table 1.654, a significance value of 0.000 <0.05 and the t-count value of the X2 variable 9.282 > t table 1.654, a significance value of 0.000 <0.05 (2) there is an influence significant simultaneously from service quality and customer value to customer satisfaction PT. Banyuwangi Eternal Prosperous Star Award is proven by the calculated F-value of variables X1 and X2 48.371 > F table 3.055 and a significance value of 0.000 <0.05.